Editorial for the Special Issue on Recent Advances in Thin Film Electronic Devices - Chengyuan Dong (Micromachines, 2022)
Thin film electronic devices have been attracting more and more attention because of their applications in many industry fields, such as in flat panel displays (FPDs), energy devices, sensors, memories, and so on [...]